USING USER-FRIENDLY DIGITAL MODE FOR ARABIC LANGUAGE TEACHERS, BANDUNG DISTRICT - Saleh, Nalahuddin; Abdurrahman, Maman; Maulani, Hikmah; M Khalid, shofa (Lingua, 2022)
Teaching foreign languages, such as Arabic in Indonesia, requires a very large effort from a teacher or lecturer and requires a variety of methods and media. Through this activity, teachers will be provided with various findings of innovative learning methodologies and guided by national Arabic language experts. The purpose of this service is that Arabic language teachers can be proficient in utilizing user-friendly digital modes in learning. The study used seminar and discussion methods, with the number of participants being 30 Arabic/PAI teachers in Bandung Regency. Each teacher will be trained and assisted to apply various theories presented by experts related to various digital modes of learning. The research findings show a high value in the assessment of teacher enthusiasm for training, as well as an assessment that the use of digital mode is a solution and an alternative method in teaching Arabic, especially during the pandemic. This service is expected to be the first step to continue developing user-friendly digital mode development workshops for teachers.